İMMÜNOSÜPRESSİF İLAÇ OLAN MİCOPHENOLATE MOFETİL'İN STENT SONRASI GELİŞEN İNTİMAL HİPERPLAZİ ÜZERİNDEKİ ETKİSİ - TIRIKLI, ABDULLATİF (Fırat Üniveristesi, 2004)
l.OZET Neointimal hiperplazi, stent-içi restenozda ağırlıklı mekanizmadır. Stent-içi restenozu önlemek, düz kas hücrelerinin hiperplazisini azaltmak ile mümkündür. Biz bu çalışmayı, oral olarak uygulandığında, mikofenolat mofetilin (MMF) stent-içi neointimal hiperplaziyi inhibe edebileceği hipotezini test etmek için planladık. Çalışmaya 14 adet Yeni Zelanda tavşanı dahil edildi. Tavşanlar iki gruba ayrıldılar. Grup 1 ağız yoluyla 50mg/kg/gün aspirin, 17.5mg/kg/gün klopidogrel ve 40 mg/kg/gün MMF uygulanan 7 tavşandan oluştu. Grup 2 ağız yoluyla 50mg/kg/gün aspirin, 17.5mg/kg/gün klopidogrel verilip, MMF verilmeyen 7 tavşandan oluşturuldu. Örnekleme materyali stent öncesi ve sonrası 5 mm'lik bir alam içerecek şekilde, arter kesileri ile elde edildi. Grup l'de, stent kenarından alman örneklerde fokal neointimal hücre çoğalması izlendi. Neointimal kalınlık 0.048 ± 0.009 mm ve neointimal alan 0.0925 ± 0.019 mm2 idi. Grup 2'de belirgin neointimal hücre çoğalması ve intimal tabakada kalınlaşması izlendi. Stent kenarında neointimal kalınlık 0.147 ± 0.051 mm ve neointimal alan 0.154 + 0.023 mm2 idi. İki grupta stent kenarlarında neointimal kalınlık ve alan karşılaştırıldığında aradaki fark istatistiksel olarak anlamlıydı (p=0.001 ve alan için p=0.001). Grup l'de stent-içi arter örneklerinde bazı olgularda neointimal hücre çoğalması izlenmezken bazılarında çok sınırlı fokal intimal kalınlaşma mevcuttu. Neointimal kalınlaşma 0.071 ± 0.003 mm ve neointimal alan 0.073 + 0.003 mm2 idi. Grup 2'de ise stent içinde belirgin ve çoğunlukla fokal neointimal hücre çoğalması ve intimal tabaka oluşumu izlendi. Neointimal kalınlaşma 0.154 ± 0.069 mm ve neointimal alan 0.279 ± 0.059 mm2 idi. İki grubun karşılaştırılması istatistiksel olarak belirgin fark gösteriyordu (kalınlık için p=0.011 ve alan için p=0.001). Üçüncü ayda her iki grupta da endotelizasyon tamamlanmıştı. Sonuç olarak, oral MMF kenar etkisi olmaksızın stent-içi intimal hiperplaziyi azaltmaktadır. Stent-içi restenozu önlemek için insanlarda da sistemik immunosüpresif tedavi çalışmaları yapılmalıdır.

The Effect Of Micophenolate Mofetil, Ân Immunosuprassive Drag, On Intimal Hiperplasia After Stenting Neointimal hyperplasia is in the forefront in in-stent restenosis. Prevention of in-stent restenosis is possible by reducing and inhibiting the hyperplasia of smooth muscle cells. We planned this study to test the hypothesis that when administered orally, mycophenolate mofetil (MMF) could inhibit in-stent neointimal hyperplasia. The study included 14 New Zealand rabbits. The rabbits were allocated to two different groups. Group 1 included 7 rabbits that were given 40 mg/kg/d MMF by oral route. Group 2 included 7 rabbits that were not given MMF after the stenting. Sampling materials were taken before and after stenting by incising the artery so as to cover a 5-mm area. The samples taken from the edge of the stent in Group 1 showed focal neointimal cell proliferation, but it was lesser when compared with the control group. Neointimal thickness was 0.048 ± 0.009 mm and neointimal area was 0.0925 ± 0.019 mm2. Apparent neointimal cell proliferation and thickening of the intimal layer were observed in Group 2. Neointimal thickness at stent edge was 0.147 ± 0.051 mm and neointimal area was 0.154 ± 0.023 mm2. The differences between groups in terms of neointimal thickness and neointimal area were statistically significant (p=0.001 for thickness and p=0.001 for area). In-stent artery samples of Group 1 showed that some subjects had no neointimal cell proliferation, while others had very limited focal intimal thickening. Neointimal thickening was 0.071 ± 0.003 mm and neointimal area was 0.073 ± 0.003 mm2. In Group 2 apparent and mostly focal, neointimal cell proliferation and formation of intimal layer were observed in the stent. Neointimal thickening was 0.154 ± 0.069 mm and neointimal area was 0.279 ± 0.059 mm2. The comparison between groups showed significant differences (p=0.011 for thickness and p=0.001 for area). It was established in the third month that endothelization was completed in both Group 1 and Group 2. As a result, oral MMF decreased in-stent intimal hyperplasia without edge effect. It was concluded that for the prevention of in-stent restenosis studies should be conducted for using systemic immunosuppressive treatments in humans as well. Key words: mycophenolate mofetil, in-stent intimal hyperplasia
The effect of micophenolate mofetil, an immunosuprassive drug, on intimal hiperplasia after stenting
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Kardiyoloji; Cardiology